2021
DOI: 10.1016/j.cjco.2021.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Mandating Training Is Not Enough: The State of Cardiopulmonary Resuscitation and Automated External Defibrillator Training in Ontario Schools

Abstract: Cardiopulmonary resuscitation (CPR) and automated external defibrillator (AED) training in schools are mandated in the Ontario high school curriculum. We surveyed schools to understand the scope of this training, including its barriers and facilitators. We recruited 120 (58.5%) elementary, 25 (12.2%) middle, and 60 (29.3%) high schools. Almost 60% (120 of 200) provided staff with CPR training, but only 56% (27 of 48) of high schools trained students. Major barriers included lack of funding, time, and trainers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
1
6
0
1
Order By: Relevance
“…The frequent presence of multiple lay rescuers at organised sporting events or within exercise facilities presents the opportunity to maximise the provision of bystander interventions, increasing the probability of survival after exercise-related SCA. Evidence has shown that in many sport and exercise settings, satisfactory plans are not in place to effectively respond to a cardiac event 15–21 24 75–77. Our review strengthens the need to further reduce the chance of a catastrophic outcome after exercise-related SCA through the development and rehearsal of emergency action plans at institutions, exercise facilities and during organised sporting events 9 11 12.…”
Section: Discussionsupporting
confidence: 53%
“…The frequent presence of multiple lay rescuers at organised sporting events or within exercise facilities presents the opportunity to maximise the provision of bystander interventions, increasing the probability of survival after exercise-related SCA. Evidence has shown that in many sport and exercise settings, satisfactory plans are not in place to effectively respond to a cardiac event 15–21 24 75–77. Our review strengthens the need to further reduce the chance of a catastrophic outcome after exercise-related SCA through the development and rehearsal of emergency action plans at institutions, exercise facilities and during organised sporting events 9 11 12.…”
Section: Discussionsupporting
confidence: 53%
“…This is somewhat consistent with the recent literature. 9 , 11 , 20 , 22 Many studies documented a positive association with teachers’ willingness levels 10 , 20 , 23 , 24 and only one study found a link between perceived control behaviour and CPR implementation in school. 9 …”
Section: Discussionmentioning
confidence: 99%
“…This is somewhat consistent with the recent literature. 9,11,20,22 Many studies documented a positive association with teachers' willingness levels 10,20,23,24 and only one study found a link between perceived control behaviour and CPR implementation in school. 9 As for CPR training barriers, legal liability seems to be a worldwide concern.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations